Epistemologi Hadis Dalam Perspektif Kelompok Syiah dan Khawarij - Nikmah, Shofiatun (Al Mabhats : Jurnal Penelitian Sosial Agama, 2019)
The divisions of the Muslims which are motivated by power politics develop in the epistemology of each group in understanding religion. Including the way they look at the Qur'an and hadith. Hadiths are considered more complex in their development and dissemination than the Qur'an. Shia and Khawarij also have different epistemologies in understanding the hadith. the Shi'ah legitimizes all the hadith narrated by the twelve imams without requiring the conditions for the continuation of sanad as per the conditions set by the Sunni scholars in evaluating the hadith. The Shi'ah believe that the hadith narrated by the Twelve Imams is an inspiration from Allah. The khawarij set strict standards in accepting the traditions, but on the other hand the khawarij accept the ahadith Ahad which textually support their beliefs and creeds. The second epistemology in viewing the hadith cannot be scientifically justified because the hadith is made as a legality for the interests and understanding of their groups.